Multinational business finance - Eiteman, David K.; Stonehill, Arthur I.; Moffett, Michael H. (Boston : Pearson Prentice Hall, 2010)
Globalization and the multinational enterprise -- Financial goals and corporate governance -- The international monetary system -- The balance of payments - - Current multinational financial challenges : the credit crisis of 2007-2009 -- The foreign exchange market -- International parity conditions -- Foreign currency derivatives -- Interest rate and currency swaps -- Foreign exchange rate determination and forecasting -- Transaction exposure -- Operating exposure -- Translation exposure -- The global cost and availability of capital -- Sourcing equity globally -- Sourcing debt globally -- International portfolio theory and diversification -- Foreign direct investment theory and political risk -- Multinational capital budgeting -- Multinational tax management -- Working capital management -- International trade finance.
Includes bibliographical references and index.
Keywords: International business enterprises -- Finance; Uluslararası ticaret işletmeleri -- Finans